O gesto, a forma e a cor na pintura de Tomie Ohtake - Campos, Ricardo José de (2017)
Tomie Ohtake's painting stands out in her work as the way she mostly expressed herself. Guided by an incessant search, she goes through different periods, distinct anxieties, having covered little more than sixty years of production. The discussion elicit